Knowledge Level of Medical Students Regarding Clinical Manifestasions of Autism Spectrum Disorder - Ichsanino, Muhammad Reyhan; Eka Pratiwi, Sari; Fitrianingrum, Lit (Universitas Muhammadiyah Yogyakarta, 2024)
Autism Spectrum Disorder (ASD) is a group of brain development disorders characterized by stereotyped behavior and deficits in communication and social interaction. Cases of autism in Indonesia increased by as many as 6,900 cases per year. The increase in prevalence is due to the excellent knowledge and awareness among medical students and the broad possible criteria for making a diagnosis. Therefore, this study aims to describe the knowledge level of medical students regarding the clinical manifestations of ASD. This quantitative study used a descriptive design with a total sampling method. The target population of this study was all Tanjungpura University Medical Students. The sample population selected for this study was active Tanjungpura University Medical Students, Class of 2017 and 2018, who were then filtered using inclusion and exclusion criteria. As many as 178 participants filled out a questionnaire, and the data were subsequently analyzed utilizing a statistical program with a descriptive statistical test. Knowledge was divided into three categories of levels, namely good (76-100%), fair (56-75%), and poor (≤55%). The results revealed that the knowledge level of ASD clinical manifestation of the medical students was 77% good, 11% fair, and 12% poor.